Anti-Müllerian hormone, testicular descent and cryptorchidism - Rey, Rodolfo A.; Grinspon, Romina P. (Frontiers in Endocrinology, 2024)
Anti-Müllerian hormone (AMH) is a Sertoli cell-secreted glycoprotein involved in male fetal sex differentiation: it provokes the regression of Müllerian ducts, which otherwise give rise to the Fallopian tubes, the uterus and the upper part of the vagina. In the first trimester of fetal life, AMH is expressed independently of gonadotropins, whereas from the second trimester onwards AMH testicular production is stimulated by FSH and oestrogens; at puberty, AMH expression is inhibited by androgens. AMH has also been suggested to participate in testicular descent during fetal life, but its role remains unclear. Serum AMH is a well-recognised biomarker of testicular function from birth to the first stages of puberty. Especially in boys with nonpalpable gonads, serum AMH is the most useful marker of the existence of testicular tissue. In boys with cryptorchidism, serum AMH levels reflect the mass of functional Sertoli cells: they are lower in patients with bilateral than in those with unilateral cryptorchidism. Interestingly, serum AMH increases after testis relocation to the scrotum, suggesting that the ectopic position result in testicular dysfunction, which may be at least partially reversible. In boys with cryptorchidism associated with micropenis, low AMH and FSH are indicative of central hypogonadism, and serum AMH is a good marker of effective FSH treatment. In patients with cryptorchidism in the context of disorders of sex development, low serum AMH is suggestive of gonadal dysgenesis, whereas normal or high AMH is found in patients with isolated androgen synthesis defects or with androgen insensitivity. In syndromic disorders, assessment of serum AMH has shown that Sertoli cell function is preserved in boys with Klinefelter syndrome until mid-puberty, while it is affected in patients with Noonan, Prader-Willi or Down syndromes.